Optimal STATCOM allocation using mixed Integer distributed ant colony optimization - CEYLAN, OĞUZHAN (My University, 2023)
This paper presents a novel optimization approach to find the optimal STATCOM installation in the power system using Mixed Integer Distributed Ant Colony optimization (MIDACO). The proposed method is mathematically formulated based on minimizing the Voltage Deviation Index (VDI) and the installation cost of STATCOM. The ability of STATCOM to provide shunt compensation to maintain bus voltage is exploited here. The proposed approach has been tested on the standard IEEE 14-bus system.
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarımda Enerji; Biyoyakıt Teknolojisi; Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Kontrol ve Sistem Mühendisliği; Sinyal İşleme; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Energy in Agriculture; Biofuels Technology; Information Systems, Communication and Control Engineering; Control and System Engineering; Signal Processing; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; OTOMASYON & KONTROL SİSTEMLERİ; ULAŞIM; MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; ENERJİ VE YAKITLAR; Engineering, Computing & Technology (ENG); ENGINEERING; AUTOMATION & CONTROL SYSTEMS; TRANSPORTATION; ENGINEERING, ELECTRICAL & ELECTRONIC; ENERGY & FUELS; Enerji Mühendisliği ve Güç Teknolojisi; Fizik Bilimleri; Elektrik ve Elektronik Mühendisliği; Kontrol ve Optimizasyon; Toplu taşıma; Sosyal Bilimler ve Beşeri Bilimler; Yenilenebilir Enerji, Sürdürülebilirlik ve Çevre; Energy Engineering and Power Technology; Physical Sciences; Electrical and Electronic Engineering; Control and Optimization; Transportation; Social Sciences & Humanities; Renewable Energy, Sustainability and the Environment; MIDACO; Voltage Stability